2011
DOI: 10.1016/j.tranpol.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour theory and soft transport policy measures

Abstract: The aim is to propose a theoretical grounding of soft transport policy measures to reduce car use. A general conceptual framework is first presented to clarify how hard and soft transport policy measures impact on car-use reduction. Two different behavioural theories that have been used to account for car use and car-use reduction are then integrated in a self-regulation theory that identifies three stages of the process of voluntarily changing car use, setting a car-use reduction goal, forming a plan for achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
191
1
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(218 citation statements)
references
References 51 publications
4
191
1
10
Order By: Relevance
“…They are activated when the subject is aware of the consequences of his/her own actions, deliberately taken [13] Normative believes They refer to the perceived behavioural expectations of the referent individuals or groups (parents, relatives, friends, etc.) [14,15] Subjective norms They are determined by the combination of normative beliefs with the person's motivation to comply with the different referents Allport's trait theory [17] Personality traits 16 Personality Factors No agreements emerge on the definition (see [16]) [18] Goldberg's Big Five personality traits [19] Emotional response It expresses the affective dimension of the object (e.g., car) related to a choice (e.g., modal choice) that influences such choice [20][21][22] Emotions/Personal Stories Past experience It expresses the life experiences or habits in the past (also in the early stage of life) that influence people choices [23] …”
Section: Myth Of Naturementioning
confidence: 99%
See 2 more Smart Citations
“…They are activated when the subject is aware of the consequences of his/her own actions, deliberately taken [13] Normative believes They refer to the perceived behavioural expectations of the referent individuals or groups (parents, relatives, friends, etc.) [14,15] Subjective norms They are determined by the combination of normative beliefs with the person's motivation to comply with the different referents Allport's trait theory [17] Personality traits 16 Personality Factors No agreements emerge on the definition (see [16]) [18] Goldberg's Big Five personality traits [19] Emotional response It expresses the affective dimension of the object (e.g., car) related to a choice (e.g., modal choice) that influences such choice [20][21][22] Emotions/Personal Stories Past experience It expresses the life experiences or habits in the past (also in the early stage of life) that influence people choices [23] …”
Section: Myth Of Naturementioning
confidence: 99%
“…The affective dimension tying some people to their car is not only a psychological factor but is generated by collective cultural and symbolic patterns [36,37]; such aspects were understood very early on by manufacturers, who developed emotion-targeted advertisements. In transport research, emotion as an explanatory variable of modal choice is measured in terms of anticipated emotions, that is, thoughts about future feelings after attaining a specific goal (see [20][21][22]). Emotional response shortcuts rational decision-making and past experience; notably, contact with nature at an early age explains pro-environmental orientation.…”
Section: Strengths and Weaknesses Of Application To Transport Sector mentioning
confidence: 99%
See 1 more Smart Citation
“…Bamberg et al (2011) have observed that when forming an intention to use a certain mode, people do not only take into account their attitudes toward this mode but they also: judge the perceived service performance (difficulty of using it); take into account subjective norms (perceived social pressure to engage or not to engage in a behaviour); and assess perceived behavioural control (people's perceptions of their ability to perform a behaviour). Attitudinal factors such as environmental concern and car affection (flexibility and comfort) have been identified to have significant effects (Cools et al, 2009).…”
Section: Determinants Of (Changes In) Mode Choice Behaviourmentioning
confidence: 99%
“…MaxSEM, developed within MAX-SUCCESS [29], diagnoses individuals' modal choice decisions by focusing on their attitudes towards current and future car use [30,31]. According to their responses to six statements indicating the most preferred one, and their answers to questions on travel behaviour, the respondents are defined as belonging to one of four stages in the process of changing from car use to more sustainable transport modes.…”
Section: The Analytical Toolmentioning
confidence: 99%